Current Trends of German Codetermination by Works Councils: On Path Dependencies, Erosion and Innovation - Thomas Haipeter (Industrial Relations Journal, 2025)
This article is about current developments of codetermination by works councils as a core institution of labour relations in Germany. It is argued that we can observe seven different paths of development which point into different directions, combining processes of erosion, functional change and social innovation in co-determination.
Keywords: 330; codetermination; erosion; path dependency; social innovation; trade unions; works councils